Rethinking Zimbabwean Agricultural Land Expropriation Laws in Light of the Funnekotter Case - OluSoyeju, Olufemi Olugbemiga (University of Pretoria, 2017)
This study examines whether or not the Zimbabwean agricultural land expropriation laws are consistent with its international legal commitments and obligations enumerated in Article 6 of the Zimbabwe-Netherlands BIT which were expounded in the Funnekotter case. It begins by exploring the concept of expropriation, and the main features of the Zimbabwe's agricultural land expropriation laws, and proceeds to discuss the conditions of expropriation enumerated in Article 6 using the Funnekotter case as a compass, before examining whether or not the Zimbabwe's agricultural land expropriation laws are compatible with article 6 conditions of expropriation. The main conclusion reached is that despite the good intentions and public interests pursued by these agricultural land expropriation laws, they are draconian, and inconsistent with the due process, non-discrimination, and compensation conditions of expropriation. Thus, Zimbabwe may have to re-think its agricultural land expropriation laws in light of the Funnekotter case.